A KNOWLEDGE MANAGEMENT APPROACH FOR SMALL MEDIUM ENTERPRISES (SME) - Rona Tumiur Mauli Caroline Simorangkir (Jurnal Ilmiah Manajemen dan Bisnis, 2015)
This paper was written to help identify some contradictions which can be found in the notion of knowledge management.  The author suggests that knowledge – that is to say “what we know” – can scarcely be understood and managed even by ourselves, much less by means of sophisticated information and communications (example: groupware and shareware) technologies. This paper examine the relationship between sustainable sales growth and knowledge management activities in small and medium sized enterprises (SMEs). this paper explores whether knowledge management has an influence on corporate success in small- and medium-sized enterprises (SMEs). Keyword : Management, Information, Communications, Relationship